Spunbond-Meltblown-Spunbond as a solution for surgical mask in the Covid-19 pandemic: case A98 (Research, Society and Development, 2022)
The study aimed to propose the use of SMS as a material for manufacturing the high protection A98 surgical mask, verify the material’s structure, check the technical specifications of NBR 15052 and check the direct cost of manufacturing throughout the Covid-19 pandemic. Method: descriptive exploratory research of a case study type, in a tertiary reference teaching hospital for the treatment of Covid-19. The requirements tests were based on ABNT NBR 15052. To evaluate the new use of SMS, the microstructure and morphology of the netting, Scanning Electron Microscopy was used. Results: SMS is an effective material solution for the manufacturing of surgical masks. The Meltblown layer of SMS can be an innovative design solution using adjustable pleats, with no seams at the nose and chin line, to prevent the needle holes from breaking the mask’s filter element. Different combinations of SMS use (already sterilized/new) were tested; a 40g double layer was used in the A-98 mask. The direct costs of the inputs used to produce one piece of the mask were R$0.204. Conclusion: The SMS proposal for manufacturing the surgical mask met all the requirements when compared to NBR 15052: there was no structural or morphological change in the material with two sterilization processes. The production cost was 20 times less than the market prices observed at the peak of the pandemic. The study was not of a commercial type and aimed to provide a prompt response to the greatest public health crisis seen in Brazil.